ANALISIS PERBANDINGAN PERENCANAAN TEBAL PERKERASAN KAKU DENGAN METODE BINA MARGA 2003 DAN METODE AASHTO 1993 (Studi Kasus : Jalan Raya Blora Cepu, KM 21+000-KM 22+400 Kabupaten Blora Jawa Tengah) - Hariyanto Hariyanto; Setyaningsih Setyaningsih; Bambang Bambang (JITEK (Jurnal Ilmiah Teknosains), 2021)
Road pavement planning on the Blora-Cepu highway, Blora Regency is an effort to increase the capacity and quality of road services which aims to improve the smoothness, comfort and safety of driving on the road, increasing economic growth, industry and infrastructure in Blora Regency. apart from the increase in population from year to year and influenced by the movement of human and goods mobility both in the city center and in the region, so that road improvement in Blora Regency is important in supporting the smooth running of transportation and other fields. In order to solve this problem, in this case the researcher tries to analyze the thickness of the rigid pavement on the Blora-Cepu road section using the 2003 Bina Marga method and the AASHTO 1993 method. Raya Blora-Cepu KM 21 + 000 - KM 22 + 400 Blora Regency, Central Java Province, the thickness of the pavement concrete slab using the Bina Marga 2003 method is 20,200 cm and the pavement planning using the AASHTO 1993 method is 20.828 cm or 0.628 cm different. The thickness of the sub-base layer is 12.5 cm above the subgrade.